Propagation of old and non-productive zebrafish lines using IVF technique (Journal of Laboratory Animal Science, 2024)
The laboratory zebrafish (Danio rerio) is a well-established vertebrate animal model in frontline areas of modern biology  research, including screening of therapeutic molecules and assessment of toxic chemicals. High fecundity is one of the  important reproductive traits in zebrafish females that benefit researchers in obtaining a large number of embryos for  high throughput experiments. External fertilization offers easy access to the embryos up to 5 days post fertilization  without ethical concerns whilst optical transparency of developing embryos allows for imaging of the entire embryo,  which is not practical in mammalian models. Despite being prolific breeders, laboratory zebrafish exhibit a reduction in  reproductive performance aftertwo years. In vitro fertilization, which uses frozen sperm, is an effective method for  reviving genetically modified fish lines. In this study, we attempted to us e an IVF approach to re store zebrafish lines  from aged zebrafish. A total of 12 zebrafish lines were reproduced using the IVF procedure, including aged fish that are  unable to spawn naturally. A total of 974 (66.96%) and 1438 (55.67%) embryos survived utilizing the IVF procedure with  germ cells from both mutant and wild-type parents, respectively. Zebrafish embryos survived at a rate of 67.34% in the  2–3-years age groupand55.48% in the 3-4 years age group.
Keywords: Zebrafish; CWR; mutant; IVF